"THE ROLE OF NON-MONETARY RECOGNITION IN ENHANCING EMPLOYEE MOTIVATION " - S, Dhharini.; B , Premkumar (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
Employees are valued as the human capital of any organisation. Employees who are motivated and fulfilled are more likely to accomplish their responsibilities well. Employees who lack motivation are more likely to Employees that put forth minimal effort, create low-quality work, shun the workplace, and even leave for better possibilities. Motivated employees tend to be more determined, inventive, and competent. Motivated workers exhibit contentment, dedication, and enthusiasm at work, leading to optimal retention, loyalty, and harmony. These characteristics greatly enhance the organization's growth and development. This research aims to assess the influence of non-monetary incentives on employees with the help of many literatures reviews